Mountain hostage - White, Hope (Love inspired suspense., 2020)
"After an ambush during a mountain hike, Zoe Pratt ends up shoved off the mountain and her friend kidnapped. Enigmatic search and rescue volunteer Jack Monroe tracks Zoe with the help of his K-9 partner, Romeo, but as the only witness to the attack, she's far from safe. With Jack's help, can she find her friend and take down her would-be killer?" -- Page [4] cover.